2021
DOI: 10.3389/fmicb.2021.706758
|View full text |Cite
|
Sign up to set email alerts
|

Herbal Extract Mixture Modulates Intestinal Antioxidative Capacity and Microbiota in Weaning Piglets

Abstract: Recently, herbal extracts have been applied in multiple aspects, such as medicine and animal feed. Different compositions of herbal extract mixture (HEM) have various components and diverse functions. This study aimed to evaluate the effects of HEM (Lonicera japonica, Astragalus membranaceus, Eucommia folium, and Codonopsis pilosula) on intestinal antioxidant capacity and colonic microbiota in weaned pigs. A total of 18 piglets [Duroc × (Landrace × Yorkshire)] with the initial body weight of 5.99 ± 0.13 kg (we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 45 publications
1
10
0
Order By: Relevance
“…It has been reported that a negative correlation exists between the pH and SCFA concentration [27]. During fermentation, the OD 600 value of the control group was the lowest, and the intestinal bacteria consumed SCFAs, [28] causing the SCFA concentration in the GM and GMOS groups to be lower than that of the control group. Nevertheless, it was found that the GMOS was better in promoting the production of SCFAs, therefore, the reduction in polymerization did provide a beneficial effect on the prebiotic activity of GMOS.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…It has been reported that a negative correlation exists between the pH and SCFA concentration [27]. During fermentation, the OD 600 value of the control group was the lowest, and the intestinal bacteria consumed SCFAs, [28] causing the SCFA concentration in the GM and GMOS groups to be lower than that of the control group. Nevertheless, it was found that the GMOS was better in promoting the production of SCFAs, therefore, the reduction in polymerization did provide a beneficial effect on the prebiotic activity of GMOS.…”
Section: Discussionmentioning
confidence: 96%
“…It has been reported that a negative correlation exists between the pH and SCFA concentration [27]. During fermentation, the OD600 value of the control group was the lowest, and the intestinal bacteria consumed SCFAs, [28] causing the SCFA concentration in the GM and GMOS groups to be lower…”
Section: Discussionmentioning
confidence: 97%
“…Furthermore, numerous studies have been conducted on the effects of plant extracts such as herbal extracts [ 207 , 208 ], essential oils, and organic acids on gut microbiota and on preventing diarrhea [ 148 , 209 , 210 ]. These feed additives are being recognized because they decrease the prevalence of pathogenic microbes in the cecum of weaned piglets.…”
Section: Large Intestinementioning
confidence: 99%
“…The antimicrobial blend significantly decreased the occurrence of severe diarrhea in the weaned piglets and increased the relative abundance of beneficial bacteria while discouraging the pathogenic bacteria in the cecum [ 210 , 214 ]. Different dietary combinations of organic acids and fatty acids [ 215 ], plant extract and benzoic acid [ 216 ], or herbal mixtures [ 207 , 208 ] have been further tested and showed a positive effect in changing the large intestine microbiota, which could finally treat diarrhea in the weaned piglets.…”
Section: Large Intestinementioning
confidence: 99%
“…Recently, researchers found that the combination of CPO and AMT could re-establish the immune balance of the intestinal flora and alleviate colonic mucosal injury in mice with colitis ( 16 ). Synergistic extracts of AMT and CPO showed antioxidant activity in weaned piglets and influenced the relative proportion of Firmicutes and Bacteroidetes in the gastrointestinal tract ( 17 ). However, to the best of our knowledge, the combined effects of AMT and CPO extracts in broiler chickens have not yet been thoroughly studied.…”
Section: Introductionmentioning
confidence: 99%